Ultrastructure of sonic muscles of piranhas (Serrasalmidae). (27th January 2022) - Raick, Xavier; Thelen, Nicolas; Compère, Philippe; Parmentier, Eric
Abstract: Among piranhas, different species are able to produce sounds but not all of them use the same mechanism. In all species, the sound‐producing muscle originates on the second vertebra, but the insertion differs. Pygopristis denticulata can produce two kinds of pulsed sounds emitted in trains. Its sound production mechanism is mainly based on a muscle bundle that inserts between the two first ribs. In Catoprion mento, the anterior part of the sonic muscle inserts directly on the swim bladder. The most derived species ( Serrasalmus and Pygocentrus ) make all harmonic tonal sounds. Their sonic muscles constitute a single functional unit transversally surrounding the swim bladder. This study aims to study the ultrastructure of sonic muscles in nine species from these four genera. Epaxial muscles were compared with sonic muscles, and the sonic muscles of the different species were compared between them. Results confirmed ultrastructure modifications in the sonic muscles in comparison to epaxial muscles. Fibers of the sonic muscle are thinner and possess a thicker subsarcolemmal ring housing mitochondria. In sonic muscles, myofibrils are also proportionally less abundant, and their sarcomeres are longer and thinner. Some of these differences allows to separate basal species (e.g., P. denticulata ) from more derived species (genera Pygocentrus and Serrasalmus ) and supposedly support the observed differences in the acoustic abilities. Abstract : Piranhas are able to make sounds but not all the species rely on the same mechanism. This study aims to study the ultrastructure of sonic muscles in nine species from four genera ( Catoprion, Pygopristis, Serrasalmus, and Pygocentrus ). Results confirmed ultrastructure modifications in the sonic muscles in comparison to epaxial muscles. Fibers of the sonic muscle are thinner and possess a thicker subsarcolemmal ring housing mitochondria. In sonic muscles, myofibrils are also proportionally less abundant, and their sarcomeres are longer and thinner. Some of these differences allows to separate basal species (e.g., Pygopristis denticulata ) from more derived species (genera Pygocentrus and Serrasalmus ) and should favor observed differences in the acoustic abilities.